PENGARUH ENVIRONMENTALISME DAN PERILAKU MASYARAKAT TERHADAP TINGKAT KESEHATAN DENGAN FRAMING SEBAGAI VARIABEL PEMODERASI: STUDI KASUS DI WILAYAH KERJA PUSKESMAS SIMALINYANG - Gusman Virgo (PREPOTIF : JURNAL KESEHATAN MASYARAKAT, 2018)
Poor environmental quality is the cause of various disturbances in public health, in order to achieve optimum community health status, optimum conditions or environmental conditions are needed. In high disease Kampar is an environment-based disease. Lack of concern for the environment and behavior of clean and healthy living can lead to health problems in the community such as is ISPA and diarrhea. This study is aimed to analyze the effect of the environmentalism and the public behavior on the level of health in Puskesmas Simalinyang area when given framing information about environmental conditions. This study was conducted on may 2018 using the Desigh Experiment Quasi Experiment study. The results of this study are that there are significant differences in environmentalism and community behavior towards the level of public health after framing.